(untitled) (European Science Methodical Journal, 2023)
This article describes the life and creative path of Karakalpak folk poet Ibrayim Yusupov. A number of poems translated by Uzbek poets were subjected to hermeneutic analysis, and thoughts about the unique style of the poet’s work were included.